2y - 4x =
10
5
10
Answer: -10
Step-by-step explanation:
13r2s(2r + 4r3 – 3s3)
13r2(2rs + 4r3 – 3s4)
13r2(26r3s + 52r5 – 39r2s4)
Answer:
Option 3rd is correct
Step-by-step explanation:
GCF (Greatest common factor) is the largest number that divides the two number.
Factor
Find the GCF of the given expression.
GCF of , and is,
then;
Therefore, the resulting expression is,
Answer:
The Given Expression is
→
Option is correct option.
Answer:
5x^2 - 11x = 1
This is now in standard form, where a = 5, b = -11, and c = 1.
Step-by-step explanation:
To rewrite the equation 11x - 5x^2 + 7 = 6 in standard form, we need to rearrange the terms so that the polynomial is in descending order of degree, with no missing terms. The standard form of a quadratic equation is ax^2 + bx + c = 0, where a, b, and c are constants.
So, let's start by moving the constant term to the right-hand side of the equation:
11x - 5x^2 = 6 - 7
11x - 5x^2 = -1
Next, we can multiply both sides of the equation by -1 to make the coefficient of the x^2 term positive:
5x^2 - 11x = 1
This is now in standard form, where a = 5, b = -11, and c = 1.
Answer: 60%
Step-by-step explanation: